Depth Level Control System using Peripheral Interface Controller for Underwater Vehicle - Muhamad Fadli Ghani; Shahrum Shah Abdullah (Institute of Advanced Engineering and Science, 2013)
This research explained on a design and development of an Automatic Depth Control System for underwater vehicle. Definition of underwater vehicle is a robotic sub-sea that is a part of the emerging field of autonomous and unmanned vehicles. This project shows the implementation’s development of an Automatic Depth Control System on a test prototyping vehicle especially involved small-scale and low cost sub-sea robots. The Automatic Depth Control System assembled with mechanical system and module of electronic system for development of a controller.